On the stability of research joint ventures: Implications for collusion - Jo Seldeslachts; Tomaso Duso; Enrico Pennings (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
Though there is a body of theoretical literature on research joint venture (RJV) participation facilitating collusion, empirical tests are rare. Even more so, there are few empirical tests on the general theme of collusion. This note tries to fill this gap by assuming a correspondence between the stability of research joint ventures and collusion. By using data from the U.S. National Cooperation Research Act, we show that large RJVs in concentrated industries are more stable and hence more suspect to collusion. – – Trotz einer Vielzahl von theoretischen Studien, die zeigen, dass Kollusion durch Forschungsallianzen erleichtert werden kann, fehlen empirische Arbeiten, die diesen Zusammenhang bestätigen. Noch erstaunlicher ist die allgemein geringe Anzahl von empirischen Untersuchungen auf dem Forschungsgebiet der Kollusion. Dieser Aufsatz versucht diese Lücke zu schließen wobei unterstellt wird, dass ein Zusammenhang zwischen der Stabilität von Joint-Ventures und der Entstehung von Kollusionen besteht. Anhand von Daten des U.S. National Cooperation Research Act zeigen wir, dass große Forschungsallianzen in stark konzentrierten Branchen stabiler und daher eher der Absprache verdächtig sind.
Keywords: L24; L44; L52; 330; Research Joint Ventures; Product Market Collusion; Empirical Test